Analyzing Students’ Needs for Syllabus Design of English For Science - Wawan Cahyadin; Ela Martisa; Yustih Yasin (Universitas Cokroaminoto Palopo, 2022)
This article reports the findings of a study analyzing the needs of Physics Education students to inform the syllabus design of English for Science course. The study employed a descriptive quantitative method and focused on present situation analysis, target situation analysis, and learning situation analysis. To collect the data for these analyses, a set of questionnaires was administered to sixty-four students, two lecturers, and three graduates. Data analysis involved the use of a percentage system and rating scale. The analysis revealed some significant findings related to the students’ needs. First, the students need the fours language skills and vocabulary in general science for the syllabus design. However, by rank, the skills to prioritize consist of reading, vocabulary, speaking, and writing. In addition, the students require some specific common-core abilities related to those skills, most of which are related to reading and writing skills. Lastly, the students want to learn those skills through the content in general science. For the syllabus design of English for Science, the study suggests a combination of skills-based syllabus and content-based syllabus.